Ant (Hymenoptera: Formicidae) megadiversity of the Calima medio river basin - ALDANA DE LA TORRE, ROSA CECILIA; CHACÓN DE ULLOA, PATRICIA (Revista Colombiana de Entomología, 1999)
The Calima Medio river basin located in the northeast of the Valle del Cauca department. Darien Municipio, its a transitional life zone between tropical high wet forest and fluvial tropical forest. It is one of the most diverse places in flora and fauna in the world. This place is not well known from the invertebrates point of view. This is the first contribution to the knowledge of the ant fauna of this region. This study determines the ant composition in two latitudinal ranges, Río Azul (550 m) and Río Bravo (900 m), and three types of forest stages (nature forest. secondary regeneration forest and disturbed areas). Samples were taken between January and July 1994, using different sample techniques (tuna baits, 011111 traps. leaf lifter samples, and manual collecting). Calima media is the most ant diverse zone in the country now. with 53 genera and 227 species blowing to six subfamilies. this number represents 33% of the known species from Colombia and the 64% front Valle del Cauca. This study register for first time Bonopelta deletrix to South América; to Colombia Probolomymex Strumigenys cultrigei; Odontomachus panamensis. Prionopelta amabilis and the genera Stenammo: to Valle del Cauca for first-time were registered 53 species. Besides. seven species now described species in the scientific literature of the genera PaclnPsendonivrinex, Apterostigma, Strumigenvs (2 spp.), and one from the 11CW 1C11C1’11 of the subían] and Myrinieinae discovered recently. There were significative differences in the ant species composition between the two study areas, Río Azul and Río Bravo, the first one was the most diverse zone. Also, there were significant differences between the three types of forest stages sampled. Disturbed areas were different from both, mature forest and secondary regeneration forest. This study not only proposes perturbación indicator ant species but from the regeneration zone and well-conserved forests. This study demonstrates how Hydroelectric project Calima III will affect negatively not only la ant species composition presents, but to those organisms which have any interaction with them and- the processes in which they intervene.